Administration of chemotherapy in patients admitted to a haematology service: a best practice implementation project. (30th September 2022) - Coutinho, Verónica Rita Dias; Santos, Cristina Maria de Oliveira; Rodrigues, Catarina Isabel; Santos, Catarina Isabel Geraldes; Apóstolo, João Luis Alves; Cardoso, Daniela Filipa Baptista; Klugarova, Jitka; Klugar, Miloslav
ABSTRACT: Objectives: To promote evidence-based practices related to the prevention of adverse events associated with medication administration (only chemotherapy) in a hospital service. Introduction: The medication management process in a hospital setting is highly complex, going through multiple stages from drug selection, procurement and storage, to prescription, validation, dispensing, preparation, administration and monitoring. Methods: An evidence implementation project based on an audit and feedback approach was conducted from December 2019 to April 2021 using the JBI Practical Application of Clinical Evidence System and Getting Research into Practice. Results: The results of the baseline audit showed that the 10 audit criteria were mostly met; however, two of the criteria (criterion 6: the expiry date of medication is checked before use and criterion 7: the nurse who prepares the medication administers the medication to the patient) had low compliance (respectively, 0 and 67.9%). After identifying the barriers and implementing strategies to deal with the identified barriers, we verified a significant improvement in compliance with best practices (criterion 6 improved to 64.3% and criterion 7 to 78.6%). Conclusion: This implementation project was a success, achieving a great improvement of the implementation of evidence-based guidelines concerning the prevention of adverse events associated with medication administration in a hospital in central Portugal. More such projects should be planned to sustain the implementation of evidence-based methods to improve health outcomes, patient safety, costs and health systems.